2021
DOI: 10.1002/bit.27779
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virus purification with periodic counter‐current chromatography

Abstract: Virus‐based biologicals are one of the most promising biopharmaceuticals of the 21st century medicine and play a significant role in the development of innovative therapeutic, prophylactic, and clinical applications. Oncolytic virus manufacturing scale can range from 5 L in research and development up to 50 L for clinical studies and reach hundreds of liters for commercial scale. The inherent productivity and high integration potential of periodic counter‐current chromatography (PCC) offer a transversal soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As expected, results show that overloading the nanofibers or decreasing residence time is reflected in flowthrough losses as adsorptive capacity is exhausted. This can be minimized with applications such as continuous chromatography where media saturation is desired and loading zones composed of several interconnected adsorptive beds are used ( Araújo et al, 2007 ; Silva et al, 2015 ; Mendes et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As expected, results show that overloading the nanofibers or decreasing residence time is reflected in flowthrough losses as adsorptive capacity is exhausted. This can be minimized with applications such as continuous chromatography where media saturation is desired and loading zones composed of several interconnected adsorptive beds are used ( Araújo et al, 2007 ; Silva et al, 2015 ; Mendes et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in a PCC process using four columns during six cycles. Additionally, due to the high UV signal found in the sample detector and no visible breakthrough of AAV found in the frontal experiments, the dynamic control capabilities of the ÄKTA pcc (as reported elsewhere [ 19 , 27 , 28 ]) were not used. In this sense, a time-based loading was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, several research groups have reported on improvements to the chromatographic process realized by replacing batch operation with continuous processing alternatives. This has been demonstrated for the purification of recombinant proteins [ 10 , 11 ], mAbs [ 12 , 13 ], mAb fragments [ 14 ], viruses [ 15 , 16 , 17 , 18 , 19 ], and exosomes [ 20 ], for which different multi-column chromatography processes have been utilized. These processes operate in continuous or semi-continuous mode with distinct column configurations, enabling significant improvements regarding productivity, resin utilization, and buffer consumption while keeping product quality and yield at least similar to that obtained in batch processes.…”
Section: Introductionmentioning
confidence: 99%
“…Mendes et al reported a case of four-column MCC-based AEX chromatography (Capto Q) on capturing Adenovirus 5 (Ad5) and claimed a 24% increase in purification efficiency and a 78% decrease in column usage. [18] Additionally, Nestola et al reported a two-column SEC method to efficiently purify Ad5, which resulted in a six-fold productivity increase and > 10% overall yield increase. [19] In addition to Ad5, most recently, Mendes et al demonstrated that rAAV also could be purified continuously through a four-column MCC affinity chromatography and the authors claimed that the MCC method achieved a three-fold improvement in affinity productivity with similar virus recoveries.…”
Section: Fischer Et Al Reported a Continuous Purification Scheme For ...mentioning
confidence: 99%
“…reported a case of four‐column MCC‐based AEX chromatography (Capto Q) on capturing Adenovirus 5 (Ad5) and claimed a 24% increase in purification efficiency and a 78% decrease in column usage. [ 18 ] Additionally, Nestola et al. reported a two‐column SEC method to efficiently purify Ad5, which resulted in a six‐fold productivity increase and > 10% overall yield increase.…”
Section: Introductionmentioning
confidence: 99%